If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1X + -1y + 2z = -13 Solving -1X + -1y + 2z = -13 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add 'y' to each side of the equation. -1X + -1y + y + 2z = -13 + y Combine like terms: -1y + y = 0 -1X + 0 + 2z = -13 + y -1X + 2z = -13 + y Add '-2z' to each side of the equation. -1X + 2z + -2z = -13 + y + -2z Combine like terms: 2z + -2z = 0 -1X + 0 = -13 + y + -2z -1X = -13 + y + -2z Divide each side by '-1'. X = 13 + -1y + 2z Simplifying X = 13 + -1y + 2z
| 0=12x^2+9x+4 | | -3x+15y=5 | | 12x+9y=594 | | 588=6.50x+8.25y | | B+15=8b+8 | | 15=0.2(2+0.1) | | 3a+5=-2 | | x^2-16x+y^2-16y+103=0 | | 0=18x^2+9 | | 4x^3-108x^2+2200=0 | | t^2+4t=200 | | -a-3=2-a | | 5a+9+8=32 | | ab=b+d | | C(x)=0.64x^2+0.13x+40 | | 12-the=h+6 | | g(-6m)=x^2+5x | | 7n-5+n=4+5n | | -19+8=6m-7m-5 | | 150=[0.5(9+x)]12 | | -6+4x=42 | | 2V-14=14 | | 1+3n=10 | | X=-2T^2-22T+48 | | 2-14=14 | | -8m-7=-7m | | X+.05x=10.5 | | 24-6x=4-x | | 4+y=12x-3y | | 6x^3+26x^2+8x=0 | | F(X)=-2T^2-22T+48 | | 14y-56= |